Event-based manufacturing modeling for design of a smart equipment management system (SEMS) for semiconductor industry - Zhao, Xian. (2008)
In semiconductor manufacturing, the role of maintenance is gradually being recognized as an important factor in reducing the equipment downtime and ensuring that the equipment operates optimally to produce good quality parts with acceptable yield and throughput levels. Maintenance strategy of highly automatic-manufacturing systems has to be synchronized, collaborated and optimized together with the other manufacturing dynamics to find balanced and optimal ways to achieve better performance.